Zwitterion-functionalized MIL-125-NH2-based thin-film nanocomposite forward osmosis membranes: towards improved performance for salt rejection and heavy metal removal. (25th July 2022) - Bayrami, Arshad; Bagherzadeh, Mojtaba; Navi, Hossein; Nikkhoo, Mohammad; Amini, Mojtaba
Abstract : Incorporating zwitterion-functionalized MIL-125-NH2 nanoparticles in the rejection layer of TFN FO membranes improves their water/ion separation performance and antifouling ability. Abstract : In the current study, thin-film nanocomposite membranes (TFN-M x ) based on a zwitterion-functionalized metal–organic framework (MOF) have been developed for the forward osmosis (FO) salt-water separation process. The active polyamide layer was formed through the interfacial polymerization of the m -phenylenediamine aqueous phase (with or without the presence of MIL-125-NH-CC-Cys) and the trimesoyl chloride organic phase. In comparison with the results from the surface of the unmodified membrane, a nanofiller-incorporated TFN-M0.10 membrane represents a smoother and more wettable surface that collaborates synergically to enhance the membrane antifouling ability. Among the examined membranes, the TFN-M0.10 membrane shows the highest water flux of 39.6 LMH under the AL-DS (active layer facing draw solution) mode in 1 M NaCl as a draw solution. This performance of the optimal membrane was carried out without any increase in the specific salt flux ( J s / J w ). In the AL-FS (active layer facing feed solution) mode, the TFN-M0.10 membrane improved the selectivity by almost 30% compared to the nanofiller-free membrane. Moreover, Cu(ii ) ions' removal performance of the optimal membrane was eventually investigated. Owing to the molecular sieving character of the applied MOF and the presence of diverse functional groups on the inserted nanofillers, the modified membranes demonstrate a higher Cu(ii ) rejection value than the unmodified one. This work presents new insights into the development of TFN-FO membranes and the feasibility of using zwitterion-functionalized MOFs as a modifier.